Oil seepage and carbonate formation: A case study from the southern Gulf of Mexico. Issue 6 (15th May 2019) - Smrzka, Daniel; Zwicker, Jennifer; Misch, David; Walkner, Christoph; Gier, Susanne; Monien, Patrick; Bohrmann, Gerhard; Peckmann, Jörn
Abstract: Oil seeps from the southern Gulf of Mexico can be regarded as natural laboratories where the effect of crude oil seepage on chemosynthesis‐based communities and carbonate precipitation can be studied. During R/V Meteor cruise 114 the seep sites UNAM ( Universidad Nacional Autónoma de México ) Ridge, Mictlan Knoll and Tsanyao Yang Knoll (Bay of Campeche, southern Gulf of Mexico) were investigated and sampled for authigenic carbonate deposits containing large amounts of liquid oil and solid asphalt. The δ 13 C values of individual carbonate phases including: (i) microcrystalline matrix aragonite and calcite; (ii) grey, cryptocrystalline to microcrystalline aragonite; and (iii) clear, fibrous aragonite cement, are between −30‰ and −20‰, agreeing with oil as the primary carbon source. Raman spectra reveal that residual heavy oils from all sites are immature and most likely originate from the same reservoir. Geochemical batch modelling using the software code PHREEQC demonstrates how sulphate‐driven oxidation of oil‐derived low‐molecular to high‐molecular weight hydrocarbons affects carbonate saturation state, and shows that the oxidation state of carbon in hydrocarbon compounds and oxidation rates of hydrocarbons control carbonate saturation and precipitation at oil seeps. Phase‐specific trace and rare earth element contents of microcrystalline aragonite and calcite, grey cryptocrystalline aragonite and clear aragonite were determined, revealing enrichment in light rare earth elements for grey aragonite. By comparing trace element patterns of carbonates with those of associated oils, it becomes apparent that liquid hydrocarbons constitute an additional source of trace metals to sedimentary pore waters. This work not only demonstrates that the microbial degradation of oil at seeps may result in the precipitation of carbonate minerals, it also elucidates that trace metal inventories of seep carbonates archive diagnostic elemental patterns, which can be assigned to the presence of heavy hydrocarbons in interstitial pore waters.